Evaluation of the outdoor drying process of jatoba wood in the Amazon (Research, Society and Development, 2020)
The objective was to evaluate the drying process of jatoba wood (Hymenaea courbaril L.) in the open air. To determine the initial humidity of the wood samples of the board ends were made. To monitor the wood moisture, four control samples were used, systematically distributed in the built wood pile with dimensions of 150 cm x 25 cm x 85 cm (length x height x width). The monitoring was carried out between October and November, this period was defined based on the average time between the storage of the wood and its commercialization in the sawmills of the region. In the green wood, an average initial humidity of 50.02% was observed and at the end of the evaluation period (46 days) the pieces were 13.75% moisture. Regarding drying rates, the highest values ​​were found for wood with humidity above 30%, an expected result due to the easy movement of free water present in the fire. The following defects were observed: curving; twisting; bending in order of greater intensity of defects per part. They also presented top and surface cracks, 93.33% of which were top, and the surface cracks were evaluated only in the number of cracks per piece, in which 33.33% were not observed this defect. The results obtained in the study are tools that contribute to the planning of outdoor drying on jatoba wood.